2015
DOI: 10.1161/circheartfailure.114.001626
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Reverse Remodeling With Biventricular Versus Right Ventricular Pacing in Patients With Atrioventricular Block and Heart Failure in the BLOCK HF Trial

Abstract: Background-Biventricular pacing in heart failure (HF) improves survival, relieves symptoms, and attenuates left ventricular (LV) remodeling. However, little is known about biventricular pacing in HF patients with atrioventricular block because they are typically excluded from biventricular trials. Methods and Results-The Biventricular versus Right Ventricular Pacing in Heart Failure Patients with Atrioventricular Block (BLOCK HF) trial randomized patients with atrioventricular block, New York Heart Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The echocardiographic results of the CHART‐1 study at 52 weeks suggest that intramyocardial administration of cardiopoietic stem cells (C3BS‐CQR‐1) has a beneficial effect on LV remodelling, both on LVEDV and LVESV, during a 52‐week follow‐up. The magnitude of the decrease in LV volumes compares favourably with the effects of beta‐blockers, renin–angiotensin–aldosterone system blockers and CRT on ventricular remodelling, an effect that has been consistently associated with improved long‐term outcomes in larger studies . Of note, these significant effects of cardiopoietic cell therapy were obtained upon a background of maximally‐tolerated standard‐of‐care therapy, where the vast majority of patients were treated with ACEi or ARBs, beta‐blockers and CRT where applicable .…”
Section: Discussionmentioning
confidence: 99%
“…The echocardiographic results of the CHART‐1 study at 52 weeks suggest that intramyocardial administration of cardiopoietic stem cells (C3BS‐CQR‐1) has a beneficial effect on LV remodelling, both on LVEDV and LVESV, during a 52‐week follow‐up. The magnitude of the decrease in LV volumes compares favourably with the effects of beta‐blockers, renin–angiotensin–aldosterone system blockers and CRT on ventricular remodelling, an effect that has been consistently associated with improved long‐term outcomes in larger studies . Of note, these significant effects of cardiopoietic cell therapy were obtained upon a background of maximally‐tolerated standard‐of‐care therapy, where the vast majority of patients were treated with ACEi or ARBs, beta‐blockers and CRT where applicable .…”
Section: Discussionmentioning
confidence: 99%
“…CRT implantation in patients with AVB accompanied by heart failure has been reported in the literature since 2005. 5,18) The publication of the results related to the BLOCK-HF study 6,7,19) confirmed that CRT could significantly improve the clinical symptoms, myocardial remodeling, and prognosis of patients with AVB accompanied by heart failure. Consistent with the above findings, the results of this study demonstrated that CRT significantly improved the myocardial remodeling and prognosis of the patients with third-degree AVB accompanied by HF.…”
Section: Discussionmentioning
confidence: 97%
“…However, in clinical practice, CRT does not show desirable efficacy in all patients with AVB accompanied by HF. The BLOCK-HF study 7) assessed the efficacy of CRT in patients with AVB accompanied by heart failure using the LVESV index (LVESVI) and found that only 43% of the patients had reductions of more than 15% in LVESVI after 12 months of biventricular pacing, while 35% of the patients had increased LVESVI, and 14% of the patients had increases of more than 15% in LVESVI. Sairaku,et al 20) compared the CRT efficacies in patients with LVEF !35% and QRS duration "120 ms, patients with treatment upgraded to CRT, and AVB patients with LVEF !…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations